Down But Not Yet Out: Depression, Political Efficacy, and Voting - Bernardi Luca; Mattila Mikko; Papageorgiou Achillefs; Rapeli Lauri (Wiley, 2022)
Depression is one of the most common health problems in the developed world. Previous research has primarily investigated the relationship between depression and voting, largely overlooking its cognitive foundations. We turn to political efficacy as a key political attitude and precondition for political engagement. We build on research into the cognitive aspects of depression to construct arguments linking depression, political efficacy, and voting. Using cross-sectional (European Social Survey) and longitudinal (U.K. Household Longitudinal Study) data, we find evidence for a negative relationship between depression and political efficacy, that depression reduces external but not necessarily internal political efficacy, and for an accumulation effect of depression on (external) political efficacy. We also show that political efficacy is a crucial mechanism for the depression–voting gap. Our research has important implications for political representation.